SISTEM INFORMASI PENGOLAHAN DATA KELAPA SAWIT BERBASIS CLIENT-SERVER - Sunardi Sunardi; Sofiansyah Fadli (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
Currently the development of information technology increasingly widespread, this is in line with the development of computers that are increasingly rapidly. Various technologies can now be created so as to facilitate all human activity. Sophistication of information technology has now become one of the requirements that must be met in order to keep up with technology. Technology and information that can not be separated from one another. But now there are many companies that have not implemented such a system because they various things. One problem is the lack of knowledge about the company's computer system, resulting in the company using the manual method, for example in the process of data processing. In this case PT. Citra Riau Sarana as one of the companies engaged in plantations, especially in the buying and selling palm oil CPO (Crude Palm Oil), which is still occurring problems in the data processing is still manual, so experiencing difficulties and frequent errors in data processing. The method used is the method of data collection by observation, interviews, library research, design models described using data flow diagrams (DAD) and entity relationship diagram (ERD). This application was built using Delphi 7 and SQL Server 2005. Applications that use the Desktop and Client-Server based, hoped to use this application the Company may reduce the level of unwanted errors and speed up data processing.